Analisis Pengaruh Karakteristik Bank, Faktor Makroekonomi terhadap Pembiayaan Sektor UMKM pada Perbankan Syariah di Indonesia - Lestari, Lutfi Bangun; Afandi, Akhsyim (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2020)
MSMEs have an important role in national economic development, but the financing of the MSME sector always fluctuates from year to year and tends to decline. This study aims to analyze the effect of bank characteristics and macroeconomic factors on the financing of the MSME sector in Islamic banking in Indonesia. This study uses time series data which is monthly data on aggregate financial statements of Islamic Commercial Banks and Sharia Business Units in Indonesia. The analysis method used in this research is Autoregressive Distributed Lag (ARDL). The results showed that the variables that affect the financing of the BUS MSME sector in the short term are ROA and BI_Rate. Whereas in the long term, the variables that affect the financing of the BUS MSME sector are the bank office network and inflation. While DPK, NPF, exchange rates, ERP both in the short term and long term have no effect on the financing of the BUS MSME sector. Then the variables that affect UUS MSME sector financing in the short term are the bank office network, ROA and BI_Rate. Whereas in the long term, the variable that affects UUS MSME sector financing is the bank office network. Meanwhile, DPK, NPF, exchange rate, ERP both in the short and long term had no effect on the financing of the UUS MSME sector.